2009
DOI: 10.1002/cae.20242
|View full text |Cite
|
Sign up to set email alerts
|

Using mobile and web‐based computerized tests to evaluate university students

Abstract: Mobile learning and testing is emerging as a potential educational environment. In this article we evaluate the use of mobile devices for testing as compared to web-based assessment systems. We also describe an authoring tool to develop adaptable and adaptive computerized tests that can be executed on such different platforms as personal computers, personal digital assistants and mobile phones. We have carried out an experiment with computer science university students to determine their satisfaction and to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 15 publications
1
39
0
1
Order By: Relevance
“…Despite the different tools used to measure student understanding, the test results are similar to what pen and paper tests would achieve after the students have become familiar with the testing devices [13,14].…”
Section: Mobile Interaction In Learningmentioning
confidence: 74%
See 1 more Smart Citation
“…Despite the different tools used to measure student understanding, the test results are similar to what pen and paper tests would achieve after the students have become familiar with the testing devices [13,14].…”
Section: Mobile Interaction In Learningmentioning
confidence: 74%
“…In addition to being used as teaching aids, online interaction tools have been used for computerized tests or quizzes to gain more accurate understanding of how well the class has understood the course material [12,13]. Despite the different tools used to measure student understanding, the test results are similar to what pen and paper tests would achieve after the students have become familiar with the testing devices [13,14].…”
Section: Mobile Interaction In Learningmentioning
confidence: 78%
“…Mobile technologies were also found to be effective in teaching and learning [15][16][17][18]. Barbosa et al reported that the use of mobile in teaching improved the learning and the interaction between students [19].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile learning reduces the complicated and repeated work of tutors and allow them to have materials that is readily available to learners even when a tutor is far away from campus [7]. In mobile learning environment, devices such as PDAs, tablets, PCs, smartphones and notebook computers have been used to enhance learning.…”
Section: Introductionmentioning
confidence: 99%